Omidubicel-Onlv: The First Commercially Available Alternative Allogeneic Hematopoietic Stem Cell Transplantation Donor Source. - Lassiter, Martha; Lail, Charlotte (Clinical Journal of Oncology Nursing, 2025)
BACKGROUND: Although allogeneic hematopoietic stem cell transplantation (alloHSCT) can be a lifesaving therapy for patients with hematologic malignancies, only 30% of patients in need of transplantation will have a human leukocyte antigen matched related donor available. OBJECTIVES: This article introduces an approved alternative donor stem cell source that is shown to provide earlier engraftment and decreased infections compared to dual or single umbilical cord blood transplantation. METHODS: This article provides an overview of the pathophysiology, clinical trial results, and nursing management of the approved omidubicel-onlv cellular therapy product as an alternative donor source for patients undergoing alloHSCT. FINDINGS: Omidubicel provides an alternative donor source for patients undergoing alloHSCT for whom there is no matched donor available. This need may be particularly great in ethnic and racial minority populations who may be underrepresented in the NMDP BioTherapies database.